Dynamical Behavior of a Nonautonomous Stochastic Modified Bazykin Model - Zhangzhi Wei; Zheng Wu; Lianglong Wang (Journal of Chemistry)
In this article, a nonautonomous stochastic modified Bazykin model is introduced. The positive solution is proved to be unique and global for any initial data via stochastic comparison theorem and Itô formula. Stochastic ultimate boundedness and stochastic permanence are also considered. Finally, some simulations are performed to verify the validity of results.